On fixed point convergence results for class of nonexpansivemappings in hyperbolic spaces via PJ iteration process - Shrivas, Jaynendra; Verma, Rohit Kumar; Chandraker, Priya (International Journal of Applied Mathematical Research, 2024)
In this paper, we provide certain fixed point results for a mean nonexpansive mapping, as well as a new iterative algorithm called PJ-iterationfor approximating the fixed point of this class of mappings in the setting of hyperbolic spaces. Furthermore, we establish strong and∆-convergence theorem for mean nonexpansive mapping in hyperbolic space. Finally, we present a numerical example to illustrate ourmain result and then display the efficiency of the proposed algorithm compared to different iterative algorithms in the literature. Our resultsobtained in this paper improve, extend and unify some related results in the literature.